EFFICACY OF DISINFECTANTS AGAINST DISEASES IN MUGA SILKWORM, ANTHERAEA ASSAMENSIS HELFER - SINGH, G.P.; GOGOI, A.K.; SAHU, A.K.; GIRIDHAR, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
Sodium hypochlorite (NaOCl), Slaked lime (Calcium hydroxide (Ca(OH)2), Urea (CO(NH3)2) and Trisodium Orthophosphate (Nas PO) tested individually and in their combination against muga silkworm Antheraea assamensis Helfer diseases. All disinfectant tested except Urea found effective in reducing the larval mortality due to diseases significantly (P<0.05) than control. The disinfectants Trisodium Orthophosphate (2.0%) in combination of urea (1.0%) and slaked lime (0.5%) and Sodium hypochlorite (0.02%) in combination of urea (1.0%) and slaked lime (0.5) were found more effective and reduced the larval mortality due to diseases and enhanced cocoon productivity significantly (P<0.05). Lowest larva mortality due to diseases was recorded 1.0% in Jethua commercial crop to 19.9% in Bhodia seed crop rearing and pooled mortality of four crops 6.38% was recorded when rearing field was disinfected by Trisodium Orthophosphate (2.0%) in combination of urea (1.0%) and slaked lime (0.5%) followed by Sodium hypochlorite (0.02%) in combination of urea (1.0%) and slaked lime (0.5%) with 1.0 to 20.0% mortality in different rearing crops and pooled mortality of four crops 7.03%. Similarly cocoon yield was recorded highest 18 to 83 cocoons/dfl (pooled of four crops 48 cocoons/dfl) and 18 to 80 cocoons/df. (pooled 47 cocoons/dfl) with the disinfection treatment of Trisodium Orthophosphate (2%) in combination of urea (1%) and slaked lime (0.5%) and Sodium hypochlorite (0.02%) in combination of urea (1%) and slaked lime (0.5%), respectively. Gain of cocoons/dfl over control Was recorded 14 and 15 cocoons/df.